Peran Guru sebagai Teladan dalam Implementasi Nilai Pendidikan Karakter - Martina Napratilora; Mardiah Mardiah; Hendro Lisa (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
In education, an exemplary and character teacher at school has a real impact on the child's personality in the future. Character building is a collective commitment of the Indonesian people to face today's global demands. The implementation of character education is a way to build a more moral education. The purpose of writing this article was to describe and analyze the exemplary teachers in implementing character education. This article had analyzed and reviewed the works of literature that were related to the topic. The model used was a library research approach. The results examined that the implementation of character education in schools is the responsibility of all school members. However, teachers play a more important role in achieving the program, the success of character education in schools depends on the extent to which the teachers can be a model for their students. Creating a character student will need a character teacher as well.